Multiband fractal planar inverted F antenna (F-PIFA) for mobile phone application - Saidatul, N.A.; Azremi, Abdullah Al Hadi; R. Badlishah, Ahmad, Prof. Madya Dr.; Soh, Ping Jack; Fareq, Malek (EMW Publishing, 2010)
Link to publisher's homepage http://ceta.mit.edu/PIERB/